Beyond bronchial thermoplasty – where to now? - Peter B. Noble; David Langton; Chuan T. Foo; Bruce R. Thompson; Alvenia Cairncross; Michael J. Hackmann; Francis Thien; Graham M. Donovan (EClinicalMedicine)
Summary: With the impending ‘retirement’ of bronchial thermoplasty (BT) for the treatment of patients with asthma, there is much to learn from this real-world experiment that will help us develop more effective future therapies with the same primary target i.e., airway smooth muscle (ASM) remodelling. This viewpoint discusses initial controversy surrounding BT (lack of an effect on forced expiratory volume in 1 s), its underutilisation, and importantly how non-standard diagnostics successfully demonstrated therapeutic response which escaped traditional lung function metrics. It is anticipated that the next iteration of BT (likely in a drug form) will have an overall greater effect on the health care system by virtue of evoking ASM remodelling as a treatable trait, and after appropriately drawing on lessons learned from the ∼fifteen-year BT saga.